2018
DOI: 10.1186/s12885-018-5139-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of factors involved in revised Tokuhashi score system for patients with spinal metastases: a systematic review and Meta-analysis

Abstract: BackgroundCancer patients’ survival time has obviously improved, with the development of systemic treatment techniques. However, the probability of metastases to the vertebrae has also been increased which makes some adverse effects on patients’ quality of life. The prediction of survival plays a key role in choosing therapeutic modality, and Tokuhashi Score was established as one of the most commonly used predictive systems for spinal metastases. Thus, this study was conducted to identify the prognostic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…We also found that for patients with spinal metastases, the difference in disease awareness had no signi cant impact on the survival time of patients. Compared with primary spinal tumors, spinal metastases had a worse survival and were closely related to the patient's disease conditions [34]. Therefore, the degree of disease awareness may have less in uence on the survival time of such patients, in addition to the symptoms caused by the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that for patients with spinal metastases, the difference in disease awareness had no signi cant impact on the survival time of patients. Compared with primary spinal tumors, spinal metastases had a worse survival and were closely related to the patient's disease conditions [34]. Therefore, the degree of disease awareness may have less in uence on the survival time of such patients, in addition to the symptoms caused by the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies focus on bone metastases originating from a monotumour. It has been reported that patients with bone metastases in breast, prostate and thyroid cancer have superior prognoses than those with lung and gastrointestinal cancer 16–18. Accordingly, survival is related to the characteristics of primary tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In most literature, data on bone metastases are based on a single tumor. Previous studies have reported that the prognoses of patients with breast, prostate and thyroid cancer with bone metastases are signi cantly superior to those of patients with lung and gastrointestinal cancer [16][17][18]. The survival of patients with bone metastases is related to the characteristics of their primary tumors.…”
Section: Introductionmentioning
confidence: 99%